Eu adolescente, e o outro, diferente?: uma análise das produções discursivas de alunos de uma escola particular de Fortaleza - Fontenele, Luciana Queiroz (2013)
This study aimed to analyze and problematize how socially favored teenagers are subjectified and construct discursively meanings about being a teenager nowadays. Referring to the relationship between discourse and forms of subjectivity in Foucault, it was searched, through intervention research, to problematize the constitution of the adolescents from how they place themselves within the discourses (acceptance–resistance–negotiation) that entangled the adolescence(s) in the current context. The contemporary transformations were taken into consideration, such as the technification expansion, the mass consumption and the little circulation in the city. These aspects restric the contact of the socially favored teenagers with others from lower classes, as well as the various discourses about adolescence from a place of knowledge and power. In other words, the discursive and non-discursive practices, according to Foucault, which underlie the constitution of the individuals. The locus of the research was a private school in Fortaleza and the theoretical-methodological tool was a discussion group, composed of fifteen adolescents between 13 and 15 years old, who produced a video called Conhecendo as Adolescencias. The analysis of the discourses produced and transmitted in the group was based on the studies of Foucault. In this analysis, it was possible to realize that the versions which adolescents construct about themselves and about the other adolescent are crossed by the psychological, biological, sociological, media and juridical speeches and above all by his experience as it is also entangled by such speeches. Even though, they do not identify which of these fields are the bases of their own discursive constructions, they show influence of those who construct different meanings about adolescence, taking their socioeconomic condition as criterion. The openness for the changes and negotiations in their positions, engendered in the discussion group, promoted discursive displacements, expanding the possibilities of subjective constitution for these adolescents more socially favored.